Estudo sobre a alimentação da raia de água doce Plesiotrygon iwamae (Chondrichthyes: Potamotrygonidae) na baía do Marajó - Pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2001)
The rays of the Potamotrygonidae family comprise the freshwater rays that live in rivers and lakes in several regions of South America and are found throughout the Amazon basin. They are currently grouped into three genera: Plesiotrygon, Potamotrygon, and Paratrygon. The study on feeding of P. iwamae was carried out with material collected in May, August, October and December 2000 from Colares and Cotijuba islands in the Amazon estuary. A total of 36 specimens of P. iwamae were captured. Of these, two rays remained intact and were deposited in the Ichthyological Collection of the Museu Paraense Emilio Goeldi, while the other 34 had their stomachs analyzed. In the analysis of stomach contents the food items were identified down to the lowest possible taxonomic category and for each item the measurements of: Frequency of Occurrence (%F.O.), Numerical (%N), Weight (%P), Relative Importance Index (%IRI), Repletion Index and Digestion Index. The results obtained, according to %IRl, indicate that these skates feed on: shrimps of the Palaemonidae family (66.6%), plant tissue (litter) (12.0%), amuré fish of the Gobüdae family (10.9%), crabs of the Portunidae family (8.8%), water lice of the Sphaeromatidae family (1.6%), and uricica (catfish) eggs of the Ariidae family (0.1%). The repletion level indicated that the stomachs were half full (50%) and the digestion level showed that the food items were mostly poorly digested. The results indicate that these rays have a feeding preference for shrimp and fish; they had fed shortly before capture and probably feed between tidal intervals when the current is lower.
Study on the feeding of the freshwater ray Plesiotrygon iwamae (Chondrichthyes: Potamotrygonidae) in the Marajó Bay - Pará
Keywords: Plesiotrygon iwamae; Chondrichthyes; Potamotrygonidae; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA